Welfare Reform and Immigrants: Implications for Policy - Alice Kopij (Columbia Social Work Review, 2012)
The Personal Responsibility and Work Opportunity Reconciliation Act of 1996 profoundly impacted immigrants and suggested a fundamental shift in our national stance toward immigration. This paper examines the impact of welfare reform on legal, non-citizen immigrants in the United States. It describes how welfare reform restructured the laws that determined the eligibility for benefits among immigrants, discusses changes made to these laws, and summarizes the debate over whether these changes were sufficient. It concludes with implications for policy and policy options that exist within the context of the present laws. Ultimately, through welfare reform, the government devalued the role of the immigrant and inverted the ideals of opportunity, equality, and full participation in society that, in theory if not in practice, characterize our national identity.